Meningkatkan Pemahaman Masyarakat tentang Peran Pegadaian Syariah dalam Menyukseskan Program Pemulihan Ekonomi Nasional pada Masa Pandemi Covid19 - Arif Zunaidi (LPPM Universitas Trunojoyo Madura, 2021)
During the COVID-19 epidemic, the worldwide economy was slowing down. Each country tries to normalize its economic activity through various policies or stimulants in order to be able to bounce back. Sharia pawnshops, as part of a financial institution with a function to play in contributing to economic growth, attempt to play a crucial role in the national economic recovery program, specifically with rahn pawnshop items. This service uses the lecture format by providing information about the role of sharia pawnshops in Indonesia's productivity expansion during the pandemic. This service activity is utilized for various purposes, starting with planning and progressing to monitoring and development. The purpose of this community service program is to make people more aware, notably of the role of sharia pawnsh. This service increased public understanding, and they became more aware of the government's role in trying to revive the economy through stimulus provided by non-bank Islamic financial institutions, one of which was sharia pawnshops.Keywords: Up to six keywords should also be included.